Analysis and prevention of accident-caused faults in power cable lines; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Susakova T. V. Tatyana (2017, 2017)
Title screen